Development of digital promotional media for tourism local based on the Cirarab Village community, Tangerang Regency - Prihanto, Yohannes Johny Natu; Utomo, Prio; Rinto, Frans Sahala Moshes (Community Empowerment, 2025)
This Community Service Program (PKM) was implemented to support the development of Cirarab Tourism Village, Tangerang Regency, through the use of community-based digital promotional media. The main problems faced by partners include limited understanding of MSMEs in digital marketing and a lack of promotional facilities for tourism villages. The objectives of this activity are to increase the capacity of MSME actors and PKK women's groups in utilizing technology for product promotion and to strengthen the digital identity of the village. The implementation methods included field observations, program formulation, five training sessions (business model canvas, product label design, product photography, digital marketing, and product diversification), assistance in creating a village website, and the production of a tourism profile video. The results of the activity showed an increase in participants' understanding and skills in the five training aspects, with achievements ranging from 87% to 95.7%, as well as the creation of an official website and profile video Cirarab Tourism Village. This program has had an impact on strengthening the competitiveness of MSMEs, increasing digital literacy, and establishing sustainable promotional tools. In the future, periodic assistance is needed to ensure that the management of websites, online stores, and promotional content remains consistent and keeps up with digital trends.